The future of finance : a new model for banking and investment - Choudhry, Moorad; Landuyt, Gino (Wiley finance series, 2010)
"New banking and investment business models to navigate the post-financial crisis environment. The financial crisis of 2007-2008 has discredited business models in the banking and fund management industries. In The Future of Finance, Moorad Choudhry and Gino Landuyt argue that banks must realign their business models, implying a lower return-on-equity; diversifying their funding sources; and increasing liquidity reserves. On the investment side, the authors discuss how diversification did not reduce risk, but rather amplified it, and failed to stabilize returns. The authors conclude that the clear lesson from the crisis is to know one's risk. A lesson that is best served by concentrating on assets and sectors that you understand. Examines the weaknesses in the business models of many institutions, as well as the theoretical foundation for professionals in the field of finance. Identifies the shortcomings of Modern Portfolio Theory. Addresses how investment managers can find new strategies for creating "alpha" and why they need to re-vamp their fee structures. Filled with in-depth insights and practical advice, The Future of Finance will provide bankers and investment managers with a guide to realigning their businesses in order to prosper in the post-crisis financial markets."